ANALISIS REDEWENDUNGEN (UNGKAPAN IDIOMATIS) BAHASA JERMAN KAJIAN SEMANTIS - Agus Syahid (LPPM Universitas Bumigora Mataram, 2017)
Redewendungen is a group of words that have an idiomatic meaning. This study discusses the using of Redewendungen contained in several sentences from Brigitte magazine and der Stern magazine as a semantic review. From the analysis that writers have done on the advertisement script, it can be concluded that Redewendungen has an idiomatic meaning. In the analysis found some meaning idiomatic, the are (1) metaphorical Redewendung, (2) orthonymische Redewendung, (3) allusive Redewendung, (4) remotivier bare Redewendung, (5) emotional Redewendung.